ANALYSIS OF THE CONTRIBUTION OF NEUROSCIENCE IN ENGINEERING BY INTERMEDIATE OF BIBLIOMETRY - Capita Quarto, Lucas; Maria da Fonseca Souza, Sônia; Aparecida Amiti Fabri, Karol; Luiz Teixeira Fully, Fábio; Crispim França Luquetti, Eliana (LINKSCIENCEPLACE, 2026)
A Neuroscience is a science that studies the central nervous system and its complexity. A neuroscience has propitiated in several planes in the most diverse areas of knowledge. This study quantitatively and bibliographically analytical in the data of the neuroscience analysis of the intermediate of bibliometry based on data of date of Scopus. As a result, 37 publications were found, with 7 Brazilian ones. Work involving neuroscience and skills began in 2003 and started in 2007. The universities that contributed the most publications were the Universidad Politécnica de Madrid and the Universidad Complutense de Madrid. In Brazil, the indicators started in 2004 and the Federal University of Rio de Janeiro appears in 3rd place in the world ranking. Neuroscience is a branch of knowledge that has been gaining more and more attention in scientific research; it has been noted that it is studies focused on the areas of engineering.